Legends & Lies: The Real West - Fisher, David, 1946-; O'Reilly, Bill; Wopat, Tom (New York, NY : Macmillan Audio, 2015)
A fascinating, eye-opening look at the truth behind the western legends everyone thought they knew. Included are the ten legends featured in Bill O'Reilly's 'Legends and Lies' docuseries; from Kit Carson to Jesse James, Wild Bill Hickok to Doc Holliday, accompanied by two bonus chapters on Daniel Boone and Buffalo Bill and Annie Oakley.
Keywords: Frontier and pioneer life -- Anecdotes -- West (U.S.); West (U.S.) -- Biography; West (U.S.) -- Anecdotes -- History; Audiobooks